Boundless Communication (International Journal of Engineering and Computer Science, 2016)
In the present scenario, some people need to be online all the time but it is not possible to have wired media available at everywhere. In this case Boundless media is the best solution. There are many types of boundless transmission available like radio transmission, microwaves, infrared and laser/light wave transmission. In this paper we will focus on the uses, requirements, benefits and types of unbounded communication.